Customer Perceptions of Digital Halal Certification and Its Implications for MSME Product Purchasing Decisions - Ilham Teruna Bakti; Cicih Ratnasih (Greenation International Journal of Economics and Accounting, 2025)
This study analyzes consumer perceptions of digital halal certification for MSME products and its impact on purchasing decisions. The research method uses a quantitative approach with survey techniques to 385 Muslim consumers in Central Java. The results show that 73.2% of respondents have positive perceptions of digital halal certification for MSMEs. The main factors influencing consumer perceptions include ease of digital verification (78.5%), trust in certification institutions (71.8%), and level of understanding of the certification process (69.3%). Regression analysis shows that positive perceptions of digital halal certification significantly influence purchasing decisions with a coefficient of determination value of 0.652. This research contributes to MSMEs in understanding consumer preferences for digital halal-certified products and their implications for marketing strategies.